LANDASAN PENDIDIKAN DALAM PENGEMBANGAN SISTEM PENDIDIKAN NASIONAL - Atmanegara, Weldia (CV. Lafadz Jaya, 2024)
Education is a conscious and planned effort to help students develop their physical and spiritual potential with the aim of leading them to become adults and have the ability to complete their own life tasks independently in order to achieve lifelong happiness. Meanwhile, the foundation is a place of support or starting point or basic footing. Therefore, the foundation of education is the assumptions that form the basis or starting point in the context of educational practice. The aim of education is the expected change in students' subjects after experiencing the educational process, both individual behavior and personal life as well as the life of the community in the natural surroundings where the individual lives. Meanwhile, the aim of Indonesian national education itself is to develop the potential of students to become human beings who believe in and are devoted to God Almighty, have noble character, are healthy, knowledgeable, capable, creative, independent, and become democratic and responsible citizens. Education in Indonesia has several important foundations, including legal foundations, philosophical foundations, psychological foundations, sociological foundations, cultural foundations, religious foundations, historical foundations, and technological foundations.